PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SATYA TRINADI KOMIRA PERKASA SULAWESI TENGGARA - Sandi, Sandi; Hasan, Rachmad Rialdi; Hakim, Adnan; Hartini, Hartini (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims: (1) to determine the effect of motivation and work discipline on employee performance at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi. (2) To determine the effect of motivation on employee performance at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi. (3) To determine the effect of Work Discipline on Employee Performance at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi. The population in this study is the total number of employees at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi, while the total number of employees is 45 people. Respondents in this study were 45 people. This study uses multiple linear regression analysis.The results showed that: (1) Motivation and Work Discipline had a positive and significant effect on employee performance at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi. (2) Motivation has a positive and significant effect on employee performance at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi. (3) Work Discipline has a positive and significant effect on employee performance at PT. Satya Trinadi Komira Perkasa Southeast Sulawesi.